A abordagem da variação linguística na sala de aula por professores de Língua Portuguesa do Ensino Fundamental II do município de Pé de Serra - BA - Rios, Andréa Eloína Oliveira (2016)
In this work, we analyse the approach to linguistic variation in classroom by Portuguese Language teachers from 6th to 9th grades of Elementary School in Pé de Serra city, Bahia. The main objective is to analyze how these teachers deal with the phenomenon of variation, what they understand about this process and how this knowledge is transmitted to the students. To this end, our research is based on theoretical and methodological postulates of Variationist Sociolinguistics (LABOV, 2008 [1972]; MOLLICA, 2003; among others) and Educational Sociolinguistics (BORTONI-RICARDO, 2004, 2005; GORSKI & COELHO, 2009; COELHO etalii, 2015). The results permit to see that there was a small change in some of the aspects analyzed, for example, those relating to linguistic discrimination and the concept of "error" adopted in Portuguese Language classes. However, there is still a great need to rethink pedagogical practice of teaching and learning Portuguese language concerning the work with the linguistic variation in classroom, in order to understand its meaning in the educational process.